A stable Li-deficient oxide as high-performance cathode for advanced lithium-ion batteries. Issue 15 (22nd January 2015) - Hou, Peiyu; Wang, Jie; Song, Jishun; Song, Dawei; Shi, Xixi; Wang, Xiaoqing; Zhang, Lianqi
Abstract : A stable Li-deficient Li0.35 Ni0.2 Co0.1 Mn0.7 O2− x surprisingly delivers large reversible capacity (251.3 mA h g −1 ), outstanding cycle life and a low median-voltage of 2.7 V in the range of 2.0–4.9 V. Abstract : Monodisperse Li-deficient Li0.35 Ni0.2 Co0.1 Mn0.7 O2− x spinel single crystals have been prepared for the first time. The Li-deficient oxide surprisingly delivers large reversible capacity (251.3 mA h g −1 ), outstanding cycle life and low median-voltage of 2.7 V in the range of 2.0–4.9 V. Importantly, high median-voltage (4.4 V) and superior rate capability are also obtained from 3.0 to 5.0 V. These results indicate that high-energy or high-power density can be achieved by controlling discharge cut-off voltage.